Ozone and nitrogen effects on yield and nutritive quality of the annual legume Trifolium cherleri - Sanz, J; González-Fernández, I; Calvete-Sogo, H; Lin, J S; Alonso, R; Muntifering, R; Bermejo, V (Atmospheric Environment, 2014)
Two independent experiments were performed in an Open-Top Chamber facility to determine the response of biomass and nutritive quality of the annual legume Trifolium cherleri to increased levels of ozone (O3) and nitrogen (N) deposition, two main drivers of global change. Plants growing in pots were exposed to three O3 treatments: charcoal-filtered air (CFA); non-filtered air, reproducing ambient O3 levels of the site (NFA); and non-filtered air supplemented with 40 nl l−1 (NFA+). Nitrogen was added in biweekly doses to achieve final doses of 5 (N5), 15 (N15) and 30 kg ha−1 (N30), reproducing the N deposition range in the Iberian Peninsula. Ozone negatively affected all the growth-related parameters and increased plant senescent biomass. The pollutant affected subterranean biomass to a greater extent than aerial biomass, resulting in altered aerial/subterranean ratio. Effects in the second experiment followed the same pattern as in the first, but were of lesser magnitude. However, these differences between assays could not be explained adequately by the absorbed O3 fluxes (Phytotoxic Ozone Dose, POD). Concentrations of cell-wall constituents related to nutritive quality increased with the O3 exposure, reducing the Relative Food Value index (RFV) that indicates decreased nutritive quality of the forage. Nitrogen stimulated all growth-related parameters, but increased the aboveground biomass more than the subterranean biomass. No effects of N fertilizer were detected for the nutritive quality parameters. A significant interaction between O3 and N was found in the second experiment. N further enhanced the increase of senescent biomass caused by O3. Results indicate that O3 is a potentially significant environmental stress factor in terms of structure and diversity of Mediterranean pastures.
Keywords: annual grasslands; Dehesa; Forage quality; Ozone fluxes; POD; Senescence